Ilmu Sharḥ al-Ḥadīth: Istilah dan Konsep - Muhammad Anshori (JOURNAL OF QUR'AN AND HADITH STUDIES, 2019)
This study aims to discuss the terms and methods in Sharḥ al-Ḥadīth. Literature study by referring books and relevant sources related to the theme used in this study. This research finds that the science of Sharḥ al-Ḥadīth has quite varied terms such as fiqh al-Ḥadīth, tafsīr al-Ḥadīth, garīb al-Ḥadīth, mukhtalif (ikhtilāf/mushkil) al-Hadis, ḥashiyah and ta'līq, which is each term has its own distinctions. In addition, the methods in the sharh Hadis is also various, such as taḥlīlī (analytical), ijmālī (global), muqāran (comparison/comparison), and mawdhū'ī (thematic).